Pengaruh Variasi Daya Pompa pada System Pendinginan TEG terhadap Tegangan yang Dihasilkan TEG - Hendi Lilih Wijayanto; Amiruddin Amiruddin; Kadriadi Kadriadi; Kadex Widhy Wirakusuma; Nugroho Tri Atmoko (Universitas Batanghari Jambi, 2022)
The amount of heat energy wasted on the furnace wall is of concern to researchers who are trying to utilize the heat energy wasted from a furnace wall as a generator or source of electricity. The waste heat from the combustion in the furnace can now be used as a source of electricity. The waste heat is converted into electricity using a thermoelectric generator, the TEG generator is an electrical generator device that converts heat (temperature difference) directly into electrical energy. In this research, the heat used is the cylindrical wall of the furnace with variations in the size of the pump that flows the coolant to the waterblock, to determine the efficiency and magnitude of the power pump used to cool the hot side of the TEG, which produces a high temperature difference and also produces large electrical energy. thermoelectric generator module reused 4 pieces SP1848 27145 SA module.